A szerzõdéses bizalom a hazai feldolgozóipari vállalatok üzleti kapcsolataiban (Szociológiai Szemle, 2024)
On the basis of an empirical survey, we addressed the question of whether, and how far firms of the Hungarian manufacturing sector rely on trust in their customer relations. Also, we attempted to explore the factors that influence the firms' propensity to build high-trust relationships with their customers. Our hypotheses - formulated mainly on the basis of Mari Sako's analysis of buyer-supplier relations and Karl Dieter Opp's theory on cooperation - were tested on a data set of the Hungarian manufacturing sector. We found that almost 40 per cent of the enterprises have high-trust relationships with their buyers. We have to add, however, that what we were able to measure in the survey is only a specific type of trust out of the three distinguished by Sako, namely contractual trust. The term refers to the degree of reliance on formal documents as opposed to oral agreements. The level of contractual trust was found to be influenced by the nature of the products, the type of the majority owner of the firm, and finally by the level of market uncertainty perceived by the respondent.